Sow removal patterns in commercial breed-wean herds of Midwest, USA - Malanda, Joab; Balogh, Péter; Novotni Dankó, Gabriella (Acta Agraria Debreceniensis, 2019)
An observational retrospective study was done to provide up-to-date information on recent sow removal patterns from 9 breed-wean herds of Midwest USA. The study comprised of sow’s removal reasons and removal types of F1 Landrace x Yorkshire gilts entered in the herds between 1st Jan 2014 and 31st July 2016. Data was extracted from existing database on Dec 2018 and 15% of the sows were still active in the herds hence not included in the study. Descriptive statistics showed that out of the 20,009 removed sows, planned removals comprised of farrowing productivity (FP) 3,523 (17.6%) and old age (OA) 1,785 (8.9%) while unplanned removals consisted of reproductive failure (RF) 7,786 (38.9%), health problems (HP) 2,629 (13.1%), locomotion problems (LP) 1,473 (7.4%) and conformation issues (CI) 1,350 (6.8%).‘Did not conceive’ and “No heat” were observed as the main contributing factors accounting for 37.6% and 32.9% respectively for gilts & sows removed by RF.13.5% of the gilts (Parity 0) were removed from the herds before attaining their first litter of which 64.1% of their removals was due to RF. Removal type consisted of slaughter (S) 85.0%, found dead on the farm (DoF) 10.8% and euthanized (E) 4.2%. The research findings depict an upward trend of sow RF removals in the US swine herds posing a serious concern for US swine producers. Characterization and quantification of sow removals gives a revelation on the deeper intrigues about the vulnerability of the various parity in respect to common causes of RF. This helps swine producers to decisively improve on gilt replacement selection, reproductive efficiency, health and nutrition management all aimed at increasing overall swine productivity and efficiency in management. Swine farmers in the US can now focus their efforts towards curbing unnecessary RF removal within parity specifics.